Planning As a Moral Discourse: Some Ideas For Planning Education in Indonesia - B. Setiawan (The Institute for Research and Community Services, Institut Teknologi Bandung, 1996)
This paper questions the direction of planning education which is: 1) too oriented toward the practical interest of planning profession; 2) bas ed on the planning perception which is too deterministic and too emphasis on spatial aspect; 3) not fully perceive a more broader role and position of planning in general public; and 4) ignoring the role of planning education as a place for developing planning science. Starting out from the conception that planning is also a